Mean Platelet Volume—A Predictive Factor for the Diagnosis of Nonsymptomatic Prostatitis: Results of Univariate and Multivariate Models. (January 2017) - Rifaioglu, Murat Mehmet; Demirbas, Onur; Gokce, Hasan; Davarci, Mursel
Mean platelet volume (MPV) has been reported to be related to inflammation. Prostate-specific antigen (PSA) is a protein produced by the prostate, and this protein may be elevated for several reasons, including prostatitis, benign prostatic hyperplasia, and/or cancer. The aim of the current study was to investigate the predictive effect of MPV values on nonsymptomatic prostatitis diagnosis and the relation between MPV and PSA. A total of 275 patients, 89 affected by benign prostate hyperplasia, 94 by prostate adenocancer, and 92 by prostatitis were included in the current study. PSA, total blood count parameters, and urine analysis were investigated. Findings were compared with the groups. The correlation between MPV and the other parameters were analyzed. Univariate and multivariate logistic regression analysis was performed to determine independent predictors of nonsymptomatic prostatitis diagnosis. MPV was significantly higher in patients with nonsymptomatic prostatitis than the other groups. There were negative correlations between MPV and age, total PSA or free PSA ( r = −.123; p = .042, r = −.235; p < .001, r = −.184; p = .006, respectively). According to multivariate regression model, only MPV was identified as the predictive factor for nonsymptomatic prostatitis (odds ratio: 1.451, 95% confidence interval [1.116, 1.887], p = .005). MPV, in the absence of other reasons that increased the MPV level, was significantly increased in cases with nonsymptomatic prostatitis; this increase is significantly higher than elevated PSA level in nonsymptomatic prostatitis patients. MPV could have a predictive value for the diagnosis of nonsymptomatic prostatitis.